2014
DOI: 10.1177/1557988314545485
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Health Literacy Among Korean Adults

Abstract: The role of gender in determining the level of health literacy in Korean adults is unclear. This study aimed to investigate the level of health literacy in Korean adults and identify factors associated with health literacy by gender. This study employed a cross-sectional survey design with a convenient sample of 585 community-dwelling Korean adults age19 years and older. Health literacy was measured by using eight items selected from Chew et al.’s 16-question self-reported health literacy measure. In accordanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
56
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(84 citation statements)
references
References 35 publications
24
56
0
4
Order By: Relevance
“…With regard to gender differences on health literacy, findings are mixed. While representative German surveys did not report any gender differences [27,28], there are also study findings indicating gender disparities on both functional health literacy [29] and generic health literacy [30]. Results from a national sample of British adults (n = 719) revealed that men were more likely to show a limited functional health literacy (OR: 2.04; 95% CI: 1.16-3.5) [29].…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…With regard to gender differences on health literacy, findings are mixed. While representative German surveys did not report any gender differences [27,28], there are also study findings indicating gender disparities on both functional health literacy [29] and generic health literacy [30]. Results from a national sample of British adults (n = 719) revealed that men were more likely to show a limited functional health literacy (OR: 2.04; 95% CI: 1.16-3.5) [29].…”
Section: Introductionmentioning
confidence: 77%
“…Secondly, there is a particular need for support especially for male school leaders, who are more often affected by limited health literacy than female respondents (36.5% vs. 26.9%). It is argued that these gender differences can be traced back to the traditional division of gender roles, which ascribes greater responsibility to women for the health of family members (e.g., child and elderly care) [30,57,58]. In addition, women make more frequent use of health promotion, prevention, and health care services compared to men, which could lead to women having greater health knowledge and greater routine in using the health care system [59,60].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, participants lacked information on taking medication correctly and hence medication non-compliance was observed. Patients with low health literacy have been shown to suffer less medication knowledge on how to comply with the medications for their diseases compared to those patients who have enough health literacy [11]. It is also evident in the study conducted by Zullig et al [1] that half of chronic diseases medications are estimated to be not taken as prescribed including diabetes mellitus medications.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found females in a population to exhibit significantly higher health literacy than males 41. Previous studies assessing acetaminophen knowledge have found interesting gender differences as well, including that females are more likely to inform their doctor of current acetaminophen use and more likely to know the acetaminophen content of medications and the maximum recommended daily dose of acetaminophen 42,43.…”
Section: Discussionmentioning
confidence: 99%